Penerapan Algoritma Bee Colony Optimization Dalam Pencarian Rute Tercepat Rumah Sakit di Kota Bogor - Danar Julian Pratama (STMIK Budi Darma, 2019)
Hospitals are an important part of health and are related to someone's dead life. First aid in pawing at someone who is sick is very important. Then an optimization system is needed to help patients find the shortest route to the hospital so that patients who are sick can be more efficient. This study uses the Bee Colony algorithm because it has an efficient optimization capability to solve the problem of finding the shortest route. The results obtained from this study, namely the Bee Colony algorithm can be used to find the shortest route. The more bees released the greater the chance of finding the shortest route.